STUDY OF HISTOLOGICAL FEATURES AND EXPOSURE OF HEAVY METALS IN BREAST TISSUES AND FOOD MATERIALS IN PROGRESSION OF MAMMARY TUMORS IN BREAST CARCINOMA PATIENTS - Muhammad Farooq, Marium Zafar, Ayeza Hussain, Saira, Hafiza Fizzah Riaz, Fouzia Tanvir, Sidra Aslam4, Yasir Nawaz, Ibrar Hussain, Fizza Rimal Butt, Saba Munir, Anum Saleem, Ayesha Abbas, Kirn Kashaf (Chelonian Research Foundation, 2024)
Cancer is an irregular growth of abnormal cells within body. Breast cancer is prevalent in both developed and underdeveloped countries, with higher mortality rate. Various metals are carcinogenic, contributing to develop different types of cancer. This work aimed to assess the histological characteristics of patients and investigate the role of metals in breast tissue and various food items. Clinical data were collected from Jinnah Hospital, Lahore, through questionnaires to participants who provided informed consent prior to data collection. Samples of breast tissue, soil, water, buffalo milk, chicken meat, and beef were obtained from both control and case groups and analyzed for metal accumulation using Atomic Absorption Spectroscopy. The mean age of patients was 48 years, with significant differences observed across age groups. Majority of patients were diagnosed at Stage II. Triple-negative, with invasive ductal carcinoma, was most prevalent type. More number of participants was from Lahore city, with higher frequency in urban areas than rural. Levels of heavy metals, particularly iron and zinc, were found significant impact, whereas lead did not show significant effect. In conclusion, triple-negative and invasive ductal carcinoma were most common types observed. Elevated levels of iron and zinc in breast tissue, water, and milk were associated with cancer development, in urban areas. Zinc levels were inconsistent, and lead had no significant impact. To mitigate the risk, it is crucial to enhance early detection efforts and monitor heavy metal levels in water and milk, with a focus on iron and zinc, to reduce environmental hazards.